2016
DOI: 10.1016/j.bbmt.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Impact of Secondary Failure of Platelet Recovery After Allogeneic Stem Cell Transplantation

Abstract: Secondary failure of platelet recovery (SFPR), a late decrease in the platelet count after primary platelet recovery that is not due to relapse or graft rejection, occasionally occurs after allogeneic hematopoietic stem cell transplantation (HSCT). The risk factors and impact of SFPR on transplantation outcomes are not well known in the clinical setting. Therefore, we retrospectively evaluated 184 adult patients who underwent their first allogeneic HSCT and achieved primary platelet recovery. The cumulative in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 34 publications
5
39
0
Order By: Relevance
“…PPGF was associated with shorter survival time, which is consistent with the previous studies [4,8,11,12]. Numerous studies have reported risk factors that influence platelet engraftment, such as myelotoxic agent, conditioning regimen intensity, stem cell source, and number of infused CD34 + cells or MNC [5,6,11,28].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…PPGF was associated with shorter survival time, which is consistent with the previous studies [4,8,11,12]. Numerous studies have reported risk factors that influence platelet engraftment, such as myelotoxic agent, conditioning regimen intensity, stem cell source, and number of infused CD34 + cells or MNC [5,6,11,28].…”
Section: Discussionsupporting
confidence: 87%
“…Thrombocytopenia is a common complication after allo-HSCT, and severe thrombocytopenia necessitates platelet transfusion and influences patient clinical outcome [8,11,12,26,27]. However, until now, there was no adequate therapy to promote platelet engraftment in patients after allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, persistent thrombocytopenia predicts a worse outcome than fluctuating thrombocytopenia . We previously evaluated secondary failure of platelet recovery, defined as a late decrease in the platelet count following primary platelet recovery that is not due to relapse or graft rejection and showed that the occurrence of secondary failure of platelet recovery was significantly associated with inferior overall survival (OS) . Although primary delayed platelet recovery (DPR) despite prompt neutrophil engraftment after HSCT is more common than secondary failure, only limited data are available with regard to DPR.…”
Section: Introductionmentioning
confidence: 99%
“…2 Previous studies have demonstrated that thrombocytopenia after HSCT has a uniformly dismal outcome. [3][4][5][6][7] Particularly, persistent thrombocytopenia predicts a worse outcome than fluctuating thrombocytopenia. 8 We previously evaluated secondary failure of platelet recovery, defined as a late decrease in the platelet count following primary platelet recovery that is not due to relapse or graft rejection and showed that the occurrence of secondary failure of platelet recovery was significantly associated with inferior overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%